A Systematic Literature Review: Ethos, Pathos, Logos dalam Komunikasi Publik Pidato - Darryl Valerian Pramudita; Alfrida Esther Madame Hutapea; Irwansyah Irwansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to conduct an in-depth systematic review of the concept of rhetoric in public communication, focusing on the key elements of ethos, pathos, and logos proposed by Aristotle. This research method with a comprehensive literature search was carried out using academic search engines such as Google Scholar, Sage, Taylor & Francis, and Scopus, with a time span set between 2019 and 2024. The results of the study indicate that the use of ethos, pathos, and logos elements can effectively increase audience engagement. This has also been shown to strengthen the relationship between speakers and listeners on various modern communication platforms, such as social media, webinars, and public forums. The conclusion of this study is that the use of ethos, pathos, and logos elements in speeches is very important for building effective public communication. Ethos increases the credibility of the speaker, pathos touches the emotional aspects of the audience, and logos provides a logical basis for understanding the argument. The application of these three elements together produces a persuasive and meaningful speech. Aristotle's concept of rhetoric remains relevant in various modern communication contexts, such as political, social, and religious speeches. Keywords: Ethos, Logos, Pathos, Public Communication, Rhetoric